Performance and Metabolic Demand of a New Repeated-Sprint Ability Test in Basketball Players: Does the Number of Changes of Direction Matter? - Zagatto, Alessandro M. [UNESP]; Ardigò, Luca P.; Barbieri, Fabio A. [UNESP]; Milioni, Fabio [UNESP]; Dello Iacono, Antonio; Camargo, Bruno H.F.; Padulo, Johnny (Wolters Kluwer, 2017)
Performance and metabolic demand of a new repeated-sprint ability test in basketball players: does the number of changes of direction matter? J Strength Cond Res 31(9): 2438-2446, 2017 - This study compared 2 repeated-sprint ability (RSA) tests in basketball players. Both tests included 10 × 30-m sprints, with the difference that the previously validated test (RSA 2COD) featured 2 changes of direction (COD) per sprint, whereas the experimental test (RSA 5COD) featured 5 CODs per sprint. Test performances and metabolic demands were specifically assessed in 20 basketball players. First, RSA 5COD test-retest reliability was investigated. Then, RSA 2COD, RSA 5COD sprint times, peak speeds, oxygen uptake (Vo 2) and posttest blood lactate concentration [La - ] were measured. The RSA 5COD results showed to be reliable. RSA 2COD performance resulted better than the RSA 5COD version (p < 0.01), with shorter sprint times and higher peak speeds. Over sprints, the tests did not differ from each other in terms of Vo 2 (p > 0.05). Over whole bout, the RSA 2COD was more demanding than the RSA 5COD, considering overall metabolic power requirement (i.e., VO 2 -driven + [La - ]-driven components). Given that RSA 5COD (a) mimics real game-play as sprint distance and action change frequency/direction and (b) has the same metabolic expenditure per task completion as metabolic cost, RSA 5COD is a valuable option for players and coaches for training basketball-specific agility and assessing bioenergetic demands.
Keywords: action change; energy expenditure; game-play; shuttle sprints; team sport